The efficiency of OLS estimator in the linear regression model with spatially correlated errors - Butte Gotu (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1999)
Bounds for the efficiency of ordinary least squares relative to generalized least squares estimator in the linear regression model with first order spatial error process are given.
Keywords: 519; Ordinary least squares; Generalized least squares; Efficiency; Spatial error process; Spatial correlation